(3LegQI CTYGQ GdYQHs - (3eMeO Hf CHj GdNWGH GdbQTj , CHh RjO , GHf CHj GdNWGH,J (B170 (3g` s
(3ChdgG (B:s
(3cJGH LegQI CTYGQ GdYQH ai GdLGgdjI hGdESdGe GdPjf RehG heOMhG hfRd GdbQBf Ydi CdSfJge s
(3BNQgG (B:s
(3bGd GdeaVd (B: (3ghdGA TYQGA GdYQH ai GdLGgdjI hGdESdGe Chdge eQD GdbjS hBNQge GdWQeGM Ke CeJKd GdfGS CdaGXge heYGfjge Zdi gPg GdZGjI Je GdcJGH s
(3HebGQfI GdfSNI HeWHhYJi GdbGgQI (B1926 (3hHjQhJ (B1963 (3hLOJ ajgG HYV GdRjGOGJ hGdTQhMs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B114 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B281s
Keywords: (3GdCOHs